1985
DOI: 10.1016/0002-9149(85)90583-1
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of intravenous nisoldipine on left ventricular function and coronary hemodynamics

Abstract: The hemodynamic effects of nisoldipine were investigated in 16 patients with suspected coronary artery disease who underwent routine cardiac catheterization. Nisoldipine was given intravenously in a dose of 6 pg/kg over 3 minutes and measurements made before and after drug administration during spontaneous and matched atrial paced heart rate. During sinus rhythm, nisoldipine produced a significant increase in heart rate (19%, p <10m5). Left ventricular systolic pressure decreased 28 % (p <10W6) and left ventri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

1987
1987
1993
1993

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 13 publications
2
16
0
Order By: Relevance
“…Our findings are in agreement with those of Perez et al [10], who found that in open chest dogs, intravenous infusion of nisoldipine abolished the vasoconstriction of large coronary arteries induced by topical application of potassium ion; Drexler et al [9] also reported that intravenous infusion of nisoldipine in rats induced a significant va sodilatation of coronary arteries during rest and exercise. Nisoldipine also increases col lateral blood flow to the ischemic zone in acutely occluded left anterior descending coronary arteries of dogs [27], The effect of nisoldipine was recently studied in patients with coronary artery diseases at rest and dur ing exercise [5,28], It induced coronary and peripheral vasodilatation without negative inotropic effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are in agreement with those of Perez et al [10], who found that in open chest dogs, intravenous infusion of nisoldipine abolished the vasoconstriction of large coronary arteries induced by topical application of potassium ion; Drexler et al [9] also reported that intravenous infusion of nisoldipine in rats induced a significant va sodilatation of coronary arteries during rest and exercise. Nisoldipine also increases col lateral blood flow to the ischemic zone in acutely occluded left anterior descending coronary arteries of dogs [27], The effect of nisoldipine was recently studied in patients with coronary artery diseases at rest and dur ing exercise [5,28], It induced coronary and peripheral vasodilatation without negative inotropic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Nisoldipine is one of the newer dihydro pyridine derivatives (l,4-dihydro-2,6-dimethyl-4 [2-nitrophenyl]-3,5-pridinecarbonic acid isobutyl methyl ester) which acts as powerful vasodilator by inhibiting slow channel transmembrane calcium influx [1], It reduces cardiac afterload and is a potent coronary and peripheral vasodilator [2,3], Nisoldipine is 4-10 times more potent than nifedipine in inhibiting K+-induced contrac tions of isolated vascular preparation [4], Nisoldipine may have a preferential effect on the coronary vasculature in vivo [5], For this reason, nisoldipine is useful in the treat ment of ischemic heart disease [2,6], Most of the previous studies [7][8][9] have dealt with the effect of nisoldipine on total coronary vascular resistance and coronary flow. Little is known about its effect on large coronary arteries in beating hearts.…”
Section: Introductionmentioning
confidence: 99%
“…Newer dihydropyridine calcium antagonists have also been studied using this route (Serruys et al, 1985;Campbell et al, 1985). For reasons of solubility, these drugs are often administered in a vehicle of 15% ethanol, 15% polyethylene glycol and 70% water.…”
Section: Introductionmentioning
confidence: 99%
“…However, the sec ond generation of calcium antagonists such as the dihydropyridine derivative nisoldi pine (isobutylmethyl-l,4-dihydro-2,6-dimethyl-4-(o-nitrophenyl)-3,5-pyridinc dicarbox-ylate) offers high selectivity to vascular smooth muscle [7], It also has been recently shown that nisoldipine inhibits both phasic and tonic vascular contractions induced by potassium and acetylcholine [8]. Nisoldipine induces coronary and peripheral vasodila tion in patients with coronary artery disease without major negative inotropic effect [9].…”
Section: Introductionmentioning
confidence: 99%